Neuropati Optik Toksik Alkohol: Case Report - Nur Shani Meida; Ghina Ramadhita Ulhaq (Universitas Malahayati Lampung, 2026)
ABSTRACT Alcohol can cause optic nerve damage (toxic optic neuropathy) in the eye. In Indonesia, there is currently a rise in poisoning from mixed liquor (alcohol) that mixes traditional liquor with methanol (a product of alcohol denaturation). This can cause blurred vision complaints which in advanced stages can lead to blindness. This article aims to determine the symptoms of optic nerve damage and its management. The research method is an observation of the case of a 25-year-old man who came to the eye clinic of Purbowangi General Hospital with a complaint of blurred right and left eyes since 10 days ago. The patient admitted to having drunk alcohol on New Year's Eve with his friends. The patient has frequently consumed alcohol for the past 5 years. Upon arrival, ODS visual acuity examination was found to be 1/∞ (no light perception), decreased pupillary reflex, and pale optic nerve papilla. The patient was given systemic corticosteroid medication methylprednisolone 16 mg twice daily in the morning and afternoon, ranitidine twice daily, and mecobalamin 500 mg once daily. The results of the examination after 2 weeks of treatment showed an improvement in ODS vision to 2/60 and after 1 month to 6/20. There was no further improvement in vision after a 2-month follow-up. In conclusion, the presence of blurred vision symptoms with a history of alcohol consumption may indicate toxic alcohol optic neuropathy and requires appropriate and rapid management to restore vision. Education, especially for the younger generation, is needed to avoid and stop alcohol consumption to prevent visual impairment and blindness. Keywords: Alcohol, Toxic Optic Neuropathy, Blurred Vision. ABSTRAK Alkohol dapat menimbulkan kerusakan saraf optik (neuropati optik toksik) pada mata . Di Indonesia saat ini marak terjadi keracunan minuman keras (miras) oplosan yang mencampur miras tradisional dengan metanol (produk denaturasi alkohol). Akibat hal tersebut dapat menimbulkan keluhan mata kabur yang pada tahap lanjut dapat menimbulkan kebutaan. Artikel ini bertujuan untuk mengetahui gejala kerusakan saraf optik dan tatalaksananya. Metode penelitian berupa observasi terhadap kasus seorang laki-laki berusia 25 tahun yang datang ke poliklinik mata RSU Purbowangi dengan keluhan mata kanan dan kiri kabur sejak 10 hari yang lalu. Pasien mengaku sempat minum-minuman keras saat malam tahun baru bersama teman-temannya. Pasien sudah sering konsumsi alkohol 5 tahun terakhir. Pada saat datang pemeriksaan visus ODS didapatkan visus 1/∞ (no light perception), reflek pupil menurun, papil saraf optik nampak pucat. Pasien diberikan obat kortikosteroid sistemik methylprednisolone 16 mg sebanyak 2 kali sehari pada pagi dan siang hari, ranitidine 2 kali sehari dan mecobalamin 500 mg 1 kali sehari . Hasil pemeriksaan setelah pengobatan 2 minggu, terdapat perbaikan visus ODS menjadi 2/60 dan setelah 1 bulan menjadi 6/20 . Tidak ada lagi perbaikan visus setelah follow up 2 bulan. Kesimpulannya adalah adanya gejala keluhan mata kabur dengan riwayat minum alkohol bisa menindikasi adanya neuropati optik toksik alkohol dan perlu penatalaksanaan yang tepat dan cepat untuk memulihkan visus. Perlu edukasi terutama kepada generasi muda untuk menghindari dan menghentikan kebiasaan konsumsi alkohol untuk mencegah gangguan penglihatan dan kebutaan. Kata Kunci: Alkohol, Neuropati Optik Toksik, Mata Kabur.